An analysis of factors contributing to apprenticeship and traineeship completion - Stromback, Carl; Mahendran, Anusha (eContent Management Pty Ltd, 2010)
There has been a discernable focus within many Australian industries on improving the rates of completion amongst their apprentices and trainees. This paper outlines the results of a study which involved a multivariate analysis of data relating to apprenticeship and traineeship completion, derived from a database developed by the Victorian Government. The aim of the study was to investigate the relative strength of factors contributing to an individual's likelihood to complete or not complete an apprenticeship or traineeship and the interaction between these factors. The paper also attempts to interpret the results and findings from the above analysis, as well as identify and outline other areas for further research.